58 Types of Malaysian Plants for Kidney Stone Remedies - Norhayati Muhammad,; Nur Fazira Abdul Rahim,; Muhammad Ashraf Anas, (2022)
Urolithiasis or kidney stone problem is one of the diseases that have a high prevalence and recurrence rate all over the world including Malaysia. Malaysia is well known to have rich sources of medicinal plants which have been used extensively as folklore remedies for the prevention and treatment of various health ailments since time immemorial. A survey conducted by the World Health Organization (WHO) stated that around 80% of the populations in developing countries are still depending on medicinal plants to treat various diseases due to their safety, cost-effectiveness, and readily available. This book presents a concise yet informative account of potential Malaysian plants that can be used for the treatment of urolithiasis in terms of their characteristics, traditional preparation and scientific studies that have been done previously.This book has broad data obtained from various accessible library databases and electronic searches including PubMed, Google Scholar, Scopus, Science Direct as well as conference papers. From these findings, numerous articles on relevant antiurolithiatic activity of Malaysian medicinal plants were acquired and further reviewed. There are fifty-eight (58) types of Malaysian medicinal plants that have been recognised to have antiurolithiatic potential from traditional practices and scientific studies worldwide. Most of the Malaysian medicinal plants are traditionally prepared using the decoction method and possess good antiurolithiatic activities that have been proven scientifically. Aloe vera (lidah buaya), Manilkara zapota (ciku) and Melastoma malabathricum (senduduk ungu) are thought to be the most effective plants for treating urolithiasis with more than 90% inhibition and dissolution of calcium oxalate (CaOx) stones.